Analysis of Factors Causing Delays in the Implementation of the 500 L/D Water Treatment Plant Project in Duriangkang, Batam - Denok Suhartini; Adi Prawito; Koespiadi Koespiadi (THE SPIRIT OF SOCIETY JOURNAL : International Journal of Society Development and Engagement, 2025)
Batam Development Authority has initiated the construction of a new Water Treatment Plant (WTP) at the Duriangkang Reservoir with a production capacity of 500 liters per second. The project aims to address the increasing demand for clean water driven by rapid population growth, urban expansion, and industrial development. However, the project has experienced implementation delays, prompting the need to identify the main contributing factors, determine the most dominant factor, and propose solutions to mitigate future delays. Using a mixed-methods approach, this study combines qualitative and quantitative analysis through a descriptive–analytical survey method. Data were collected using questionnaires distributed to project stakeholders, including the project owner, supervising consultants, contractors, and relevant government agencies. The findings indicate that financial constraints are the most dominant factor influencing project delays, with a T-Statistic of 3.256 and a P-Value of 0.001. Other important factors include managerial issues, material shortages, and labor availability, while equipment availability is found to have no significant impact. Statistical analysis using SmartPLS 4 confirms the reliability and validity of the constructs, with financial, material, and managerial aspects playing a particularly important role in project implementation. This study provides a theoretical contribution to the body of knowledge on construction project management and offers practical insights for government institutions and stakeholders in mitigating delays in future infrastructure projects.